Fast calculation of computer-generated hologram for RGB and depth images using wavefront recording plane method - Okada, Naohisa; Shimobaba, Tomoyoshi; Ichihashi, Yasuyuki; Oi, Ryutaro; Yamamoto, Kenji; Kakue, Takashi; Ito, Tomoyoshi (Photonics Letters of Poland, 2014)
In a three-dimensional display by a computer-generated hologram?(CGH), fast computation of CGH is required. In this paper, in order to accelerate CGH generation, the following two methods are used; the first method is band-limited double-step Fresnel diffraction. Compared with the convolution-based diffraction, such as angular spectral method, the proposed method requires less computational time and memory. The second method is a wavefront recording plane (WRP) method which reduces the calculation amount by placing WRPs in the vicinity of the object. We succeeded in speeding up CGH calculation by combining the two methods. Full Text: PDF References T. C. Poon (Ed.), "Digital holography and three-dimensional display: Principles and Applications", Springer (2006). CrossRef S. C. Kim and E. S. Kim, "Effective generation of digital holograms of three-dimensional objects using a novel look-up table method", Appl. Opt. 47, D55–D62 (2008) . CrossRef K. Matsushima, H. Shimmel, and F. Wyrowski, "Fast calculation method for optical diffraction on tilted planes by use of the angular spectrum of plane waves", J. Opt. Soc. Am. A. 20, 1755-1762 (2003). CrossRef M. Yamaguchi, H. Hoshino, T. Honda, and N. Ohyama, "Phase-added stereogram: calculation of hologram using computer graphics technique", Proc. SPIE 1914, 25-31 (1993). CrossRef N. Okada, T. Shimobaba, Y. Ichihashi, R. Oi, K. Yamamoto, M. Oikawa, T. Kakue, N. Masuda, and T. Ito, "Band-limited double-step Fresnel diffraction and its application to computer-generated holograms", Opt. Express 21, 9192-9197 (2013). CrossRef F. Zhang, I. Yamaguchi, and L. P. Yaroslavsky, "Algorithm for reconstruction of digital holograms with adjustable magnification", Opt. Lett. 29, 1668-1670 (2004). CrossRef T. Shimobaba, N. Masuda and T. Ito, "Simple and fast calclulation algorithm for computer-generated hologram with wavefront recording plane", Opt. Lett. 34, 3133-3135 (2009). CrossRef T. Shimobaba, H. Nakayama, N. Masuda and T. Ito, "Rapid calculation of Fresnel computer-generated-hologram using look-up table and wavefront-recording plane methods for three-dimensional display", Opt Express 18 19504-19509 (2010). CrossRef J. Weng, T. Shimobaba, N. Okada, H. Nakayama, M. Oikawa, N. Masuda and T. Ito, "Generation of real-time large computer generated hologram using wavefront recording method", Opt. Express 20, 4018-4023 (2012). CrossRef T. Shimobaba, T. Kakue, N. Masuda, Y. Ichihashi, K. Yamamoto and T. Ito, "Computer holography using wavefront recording method", Digital Holography and Three-Dimensional Imaging(DH) DH2013, DTu1A. 2 (2013). CrossRef A. -H. Phan, M. -l. Piao, S. -K. Gil, and N. Kim, "Generation speed and reconstructed image quality enhancement of a long-depth object using double wavefront recording planes and a GPU," Appl. Opt. 53, 4817-4824 (2014). CrossRef P. Tsang, W. -K. Cheung, T. -C. Poon, and C. Zhou, "Holographic video at 40 frames per second for 4-million object points," Opt. Express 19, 15205-15211 (2011). CrossRef